Psychometric evaluation of a spelling test for elementary school students - Δ. Σιδερίδης, Γεώργιος; Μουζάκη, Αγγελική; Πρωτόπαπας, Αθανάσιος; Σίμος, Παναγιώτης (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF